2019
DOI: 10.1038/s41419-019-1724-9
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial androgenic action of steroidal aromatase inactivators in estrogen-dependent breast cancer after failure of nonsteroidal drugs

Abstract: Direct treatment of ER (+) breast cancer with Formestane diminishes the tumor within weeks. This is unlikely due to lack of estrogens alone. We proposed that it is the negative influence of androgens on the growth of ER(+) breast cancer. We investigated the influence of Formestane and Exemestane and of their major androgenic metabolites 4-hydroxytestosterone and 17-hydroexemestane on the proliferation of MCF-7 cells and ZR-75-1 cells. Inhibitory effects could be prevented by antiandrogens and siRNA. Activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The female SD rats were topically applied with placebo cream, 4-OHA cream, or without treatment. Because 1 g/kg was the efficacious dose of 4-OHA cream to suppress DMBA-induced tumor growth in rats ( 14 ), the high dose of 10 g/kg was used to evaluate 4-OHA cream toxicity. The serum biochemistry data showed that 4-OHA cream had no hematological or liver toxicity ( Figure 3B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The female SD rats were topically applied with placebo cream, 4-OHA cream, or without treatment. Because 1 g/kg was the efficacious dose of 4-OHA cream to suppress DMBA-induced tumor growth in rats ( 14 ), the high dose of 10 g/kg was used to evaluate 4-OHA cream toxicity. The serum biochemistry data showed that 4-OHA cream had no hematological or liver toxicity ( Figure 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…After 24 h, cells were treated by 4-OHA at a dose of 1 μM or left untreated in a 5% CO 2 incubator for the indicated time. The incubation time and the concentrations of compounds were used based on previous studies ( 14 ). At the end of incubation, 10 µl of 5 mg/ml MTT solution was added to each well.…”
Section: Methodsmentioning
confidence: 99%
“…Two studies have found distinct effects of exemestane, as compared to non-steroidal aromatase inhibitors, on circulating adipokines 39,40 , potentially due to the weak androgen effects of exemestane and its major metabolite 17-hydro-exemestane. Additionally, the metabolite 17-hydroexemestane has been shown to bind to the androgen receptor (AR) with high affinity 41 . The AR is present in human preadipocytes and adipocytes suggesting that the exemestane metabolite might contribute to down-regulate the transcription of leptin in the adipose tissue 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the predominant perspectives proposed that the presence of classical ERα and PR was fundamental to endocrine deprivation therapy, previously little evidence linked existing endocrine agents, as well as the hormone signaling transfer system, to the potent research directions and therapeutic target in the triple-negative aggressive subtype of breast cancer, which merited concentration. Steroidal AIs, such as formestane and exemestane, could conquer the endocrine resistance of nonsteroidal AI in an ER-independent but AR-dependent manner for their direct absorption into TNBC, which could be dictated by their androgenic metabolites hindering the accessibility of CCND1 by histone modification in G1/S transition ( 120 ).…”
Section: Non-canonical Mechanism Of Endocrine Agentsmentioning
confidence: 99%